Maternal and Neonatal Morbidities by Race in College-Educated Women - Adina R. Kern-Goldberger; Nigel Madden; Caitlin Baptiste; Alexander Friedman; Cynthia Gyamfi-Bannerman (Thieme Medical Publishers, Inc., 2024)
Objective Non-Hispanic black and Hispanic women experience significantly higher adverse maternal and neonatal outcomes compared with non-Hispanic white women. The purpose of this study is to explore whether disparities in obstetric outcomes exist by race among women who are college-educated.